Islam Memandang Korupsi beserta Solusinya - Pratama, Firdian Rizky; Rahib, Muhammad Akbar; Prakoso, Nugroho Joyo (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2022)
The corruption is one of the chronic obstacle in the process of economics development in Indonesia. The causes of corrupt practices are the poor character of the state apparatus and the breakdown of the Indonesian bureaucratic, political, and government systems. Therefore, this paper discusses how Islam views corruption and how Islam have solutions that can be offered to cope with the corruption cases. Some solution from Islam are preventive control like giving decent wages, prohibitation to accept bribes and gifts, recommends holding a treasure count in the first and last term of office, choosing good exemplary leaders, enforcing fair punishments and increasing control from the community so that they always adhere to the creed, morality and shari'ah itself and then the repressive control is more to heavy punishment like will be imprisoned, hand cut off, and the death penalty.